Latp solid electrolyte, preparation method and application thereof
Patent Information
- Application Number
- CN202610957601.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-09-15
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid-state battery preparation, specifically relating to an LATP solid electrolyte, its preparation method, and its application. Background Technology
[0002] With the rapid development of new energy vehicles, smart terminals, and large-scale energy storage industries, the market has placed higher demands on the energy density, safety, and cycle life of lithium-ion batteries. Traditional lithium-ion batteries use liquid electrolytes, which contain volatile and flammable organic solvents that pose serious safety hazards, easily leading to leaks, explosions, and other accidents. Simultaneously, the continuous side reactions between the liquid electrolyte and the lithium metal anode limit the commercialization of high-energy lithium metal batteries. Therefore, developing solid-state electrolyte materials to replace liquid electrolytes has become a key path to achieving high-safety, high-energy-density batteries. Among numerous solid-state electrolyte materials, oxide-based solid-state electrolytes have become a research hotspot due to their advantages such as high intrinsic thermal stability, wide electrochemical window (up to 5V), and environmental friendliness and non-toxicity. Among these, the NASICON-type LATP solid-state electrolyte stands out for its outstanding comprehensive performance.
[0003] For example, patent application CN120089815A provides a LATP solid electrolyte and its preparation method and use. The preparation method includes dry mixing LATP solid raw material, inorganic weak acid powder, and organic alcohol powder. The organic alcohol powder includes at least one of polyvinyl alcohol, polyethylene glycol, or polyacryl alcohol to obtain a mixed material. The mixed material is then sintered to obtain the LATP solid electrolyte.
[0004] For example, patent application CN119944051A discloses a method for preparing lanthanum-doped lithium borate-coated LATP solid electrolyte, including the following steps: Step S1, mixing lithium source, aluminum source, lanthanum source, titanium source, and phosphorus source, placing the mixed ingredients in a dispersant, placing it in a constant temperature water bath stirrer, heating and stirring until completely dry to obtain a mixed raw material; Step S2, sintering the mixed raw material at high temperature in air atmosphere to obtain a composite oxide; Step S3, pulverizing the composite oxide, adding lithium borate, and mixing evenly to obtain a mixture; the mass ratio of lithium compound to composite oxide is 0.01 to 0.05:1; Step S4, pressing the mixture into tablets, and sintering at high temperature in air atmosphere to obtain the finished lithium titanium aluminum phosphate material.
[0005] However, none of these solutions have resolved the problems of poor interface compatibility between the existing NASICON-type LATP solid electrolyte and lithium anode, low ion transference number, and insufficient performance caused by defects in the preparation process. Summary of the Invention
[0006] To address the problems of poor interface compatibility, low ion transference number, and insufficient performance caused by defects in the preparation process of existing NASICON-type LATP solid electrolytes, this invention provides a Sn-doped LATP solid electrolyte, its preparation method, and its application. The LATP solid electrolyte is prepared by the sol-gel method, and wet ball milling is performed by introducing a self-made liquid ball milling agent to achieve high lithium ion transference number and high ionic conductivity.
[0007] To achieve the above objectives, the specific technical solution of the present invention is as follows: This invention provides a method for preparing LATP solid electrolyte, comprising the following steps: LATP solid electrolyte precursors were prepared using the sol-gel method; The LATP solid electrolyte precursor was mixed with a liquid ball milling agent and then wet ball milled to obtain LATP solid electrolyte precursor powder. The LATP solid electrolyte precursor powder was pressed and heat-treated to obtain the LATP solid electrolyte. The liquid ball milling agent contains an imidazole hydroxyalkyl ether compound.
[0008] Preferably, the imidazole hydroxyalkyl ether compound is prepared by a ring-opening addition reaction of N-methylimidazolium with an epoxy-containing hydroxyalkyl ether compound.
[0009] Furthermore, the preparation method of the liquid ball milling agent includes: dissolving N-methylimidazole, an epoxy-containing hydroxyalkyl ether compound and a phase transfer catalyst in an organic solvent, reacting at a higher temperature, and obtaining the liquid ball milling agent through post-treatment.
[0010] Preferably, the epoxy-containing hydroxyalkyl ether compound is hydroxypropyl glycidyl ether, the imidazolyl hydroxyalkyl ether compound is 1-hydroxypropyl-3-methylimidazolyl ethoxy ether, the phase transfer catalyst is tetrabutylammonium bromide, and the organic solvent is anhydrous acetonitrile. By weight: 10-15 parts of N-methylimidazolium, 12-18 parts of epoxy-containing hydroxyalkyl ether compounds, 0.2-0.5 parts of tetrabutylammonium bromide, and 100-150 parts of anhydrous acetonitrile; The reaction is carried out at a temperature of 50-60°C for 6-8 hours.
[0011] The specific preparation method of the liquid ball milling agent is as follows, according to parts by mass: A1: According to the mass fraction, add 10-15 parts of N-methylimidazole, 12-18 parts of hydroxypropyl glycidyl ether, 0.2-0.5 parts of tetrabutylammonium bromide, and 100-150 parts of anhydrous acetonitrile to the reaction vessel and stir until homogeneous. A2: Heat to 50-60℃ and react at a constant temperature for 6-8 hours. During the reaction, the epoxy groups open to form alcohol hydroxyl groups. After the A3 reaction is completed, acetonitrile and unreacted raw materials are removed by vacuum distillation, and then dried under vacuum at a vacuum degree of 0.08-0.1 MPa and a temperature of 80-90℃ to obtain 1-hydroxypropyl-3-methylimidazolium ethoxy ether.
[0012] The reaction mechanism of this invention: The liquid milling agent (such as 1-hydroxypropyl-3-methylimidazolium ethoxyether) introduced during the ball milling process not only serves as a dispersion medium, but its hydroxyl groups and ether bonds in its molecular structure can also form hydrogen bonds with the surface of LATP precursor particles, effectively reducing van der Waals forces between particles and preventing aggregation. Simultaneously, the imidazole group has a certain coordination ability, which can slightly modify the chemical environment of the particle surface and promote Sn... 2+ / Sn 4+ Uniform doping at Ti sites optimizes Li + The structural integrity of the migration channels enhances the ion migration ability of the electrolyte at the microscopic level, thereby increasing ionic conductivity.
[0013] Furthermore, the sol-gel method includes: adding a titanium source to water, stirring to form a titanium hydroxide precipitate, washing it, and then adding it to a nitric acid solution until dissolved; then adding citric acid, a lithium source, and an aluminum source in sequence, dissolving them completely, and then adding a phosphorus source to form a sol; After standing to form a gel, the LATP solid electrolyte precursor was obtained by drying and heat treatment.
[0014] Furthermore, the lithium source is lithium nitrate, the aluminum source is aluminum nitrate nonahydrate, the titanium source is tetrabutyl titanate, and the phosphorus source is ammonium dihydrogen phosphate; The sol-gel method further includes adding a tin source before the sequential addition of citric acid, lithium source, and aluminum source; the tin source is tin tetrachloride pentahydrate. The mass ratio of the lithium source, aluminum source, tin source, titanium source and phosphorus source is 90-105:110-190:0-105:400-500:300-600.
[0015] Optionally, the water content is 1000-2000 parts by weight, and the precipitate is washed 3-5 times.
[0016] Further, the sol is stirred at room temperature for 0.5-1 h and then allowed to stand for 1-2 h to form a gel. The gel is dried at 80-100℃ for 24-48 h, and finally the dried gel is heat-treated at 600-800℃ for 3-5 h. The LATP solid electrolyte precursor is specifically prepared to obtain an electrolyte of Li. 1.3 Al 0.3 Sn x Ti1.7-x (PO4)3 (x=0~0.25) solid electrolyte.
[0017] Furthermore, the ball milling time of the wet ball mill is 2-4 hours, the ball-to-material mass ratio is 5:1~10:1, and the rotation speed is 300~500 r / min; The pressing pressure is 30-50 MPa, and the holding pressure is 5-10 min; the heat treatment temperature is 850-900℃, and the time is 3-5 h.
[0018] The present invention also provides an LATP solid electrolyte prepared by the aforementioned preparation method.
[0019] Further, the preparation of LASTP solid electrolyte sheets: The LASTP precursor powder and polyvinylidene fluoride (PVDF) were uniformly mixed at a certain mass ratio, then placed into a cylindrical mold for tableting, and pressed into tablets using a powder tableting machine. The pressure was maintained to obtain a circular solid electrolyte preform, which was then heat-treated in a muffle furnace to obtain LASTP solid electrolyte tablets. Optionally, the preparation steps of the LASTP solid electrolyte sheet are as follows: LASTP and polyvinylidene fluoride are uniformly mixed at a mass ratio of 19-20:0.5-1, then placed in a cylindrical mold for tableting, and pressed into sheets using a powder tablet press at a pressure of 30-50 MPa, holding the pressure for 5-10 minutes. A circular solid electrolyte preform with a diameter of 17-19 mm and a thickness of approximately 0.8-1 mm is obtained, which is then heat-treated in a muffle furnace at 850-900℃ for 3-5 hours to obtain the LASTP solid electrolyte sheet. Electrode fabrication and battery assembly: LASTP solid electrolyte sheet, PVDF binder and SuperP conductive agent were dispersed in N-methylpyrrolidone solvent, and the mixture was continuously stirred on a magnetic stirrer to obtain a uniform slurry. The slurry was coated on aluminum foil current collector and transferred to a vacuum oven to dry in order to remove N-methylpyrrolidone solvent. Finally, the dried electrode sheet was cut into coin cell electrode sheets using a manual slicing machine. The battery assembly was carried out in an argon-filled glove box. The above electrode sheet was used as the working electrode, and a lithium sheet with a diameter of 16 mm and a thickness of 0.6 mm was used as the counter electrode. The lithium-ion battery was assembled using CR2025 coin cell batteries to test its ion transport number and ionic conductivity. Optionally, the LASTP solid electrolyte sheet, PVDF binder and SuperP conductive agent are dispersed in 20-40 parts by mass of N-methylpyrrolidone solvent at a mass ratio of 8-10:1-2:1-2. Optionally, the mixture is placed on a magnetic stirrer and stirred continuously for 12-24 hours to obtain a uniform slurry. Subsequently, the slurry is coated on an aluminum foil current collector and transferred to a vacuum oven to dry at 80-100°C for 24-48 hours to remove NMP. Finally, the dried electrode is cut into coin cell electrode sheets with a diameter of 12-15 mm using a manual slicing machine.
[0020] Based on the above, the present invention also provides a solid-state battery, including the LATP solid electrolyte.
[0021] The beneficial effects of this invention are: This invention significantly reduces the particle size of LASTP precursor powder (down to the submicron level) by introducing a liquid ball milling agent, imidazole-based hydroxyalkyl ether compound, for wet ball milling. This increases the specific surface area and sintering activity of the powder, thereby enhancing the density and mechanical strength of the electrolyte sheet. When Sn doping is used synergistically with the liquid ball milling agent of this invention, a significant synergistic effect is achieved, increasing ionic conductivity by more than two orders of magnitude and ion transference number by more than 80%. This indicates that the liquid ball milling agent of this invention is not only a simple dispersion medium, but also a medium for achieving uniform Sn doping and optimizing Li... + The key additives for the migration channel are the core elements for achieving the excellent technical effects of this invention. Detailed Implementation
[0022] When testing the Young's modulus of solid electrolytes using atomic force microscopy (AFM), it is usually based on force modulation mode or force-distance curve technique: by controlling the probe to perform indentation tests at multiple different positions on the electrolyte surface, the deflection signal of the probe as it approaches the piezoelectric scanner is recorded, thereby obtaining the force-distance curve; then, the Hertzian contact model is used to fit the contact part of the curve, and the local Young's modulus value is calculated based on the geometry of the probe tip. To ensure data reliability, a probe calibrated with an appropriate spring constant must be selected, and the sample surface must be fully polished before testing to eliminate the influence of roughness. At the same time, multiple measurements are required to obtain a statistical average value. The present invention will be described in detail below with reference to specific embodiments.
[0023] Example 1 A method for preparing LATP solid electrolyte includes the following steps: Preparation of LASTP precursor powder: Li was prepared by sol-gel method 1.3 Al 0.3 Sn x Ti 1.7-x(PO4)3 (x=0) solid electrolyte, using reagent-grade LiNO3, Al(NO3)•9H2O, SnCl4•5H2O, and C as the Li, Al, Sn, Ti, and P sources, respectively. 12 H 28 O4Ti, NH4H2PO4, first 400gC 12 H 28 O4Ti was added to 1000g of deionized water and stirred to form titanium hydroxide precipitate. The titanium hydroxide precipitate was washed three times and transferred to an empty beaker. Then, the titanium hydroxide precipitate was added to 500g of HNO3 solution. After complete dissolution, 100g of C6H8O7•H2O, 90g of LiNO3 and 110g of Al(NO3)•9H2O were added sequentially and stirred continuously. After complete dissolution, 300g of NH4H2PO4 was added to the solution to form a sol. The mixture was stirred at room temperature for 0.5h and then allowed to stand for 1h to form a gel. The gel was placed in an 80℃ oven and dried for 24h. Finally, the dried gel was placed in a muffle furnace and heat-treated at 600℃ for 3h to obtain the LASTP precursor. 5g of zirconium balls and 1g of material, including 0.2g of liquid ball milling agent, were added and ball milled using a wet ball milling process for 2 hours at a speed of 300r / min.
[0024] In this embodiment, the liquid ball milling agent is an imidazolium hydroxyalkyl ether compound, 1-hydroxypropyl-3-methylimidazolium ethoxy ether, and the preparation method is as follows: A1: Add 10g of N-methylimidazole, 12g of hydroxypropyl glycidyl ether, 0.2g of tetrabutylammonium bromide, and 100g of anhydrous acetonitrile to the reaction vessel and stir until homogeneous. A2: Heat to 50℃ and react at a constant temperature for 6 hours. During the reaction, the epoxy group opens to form an alcohol hydroxyl group. A3: After the reaction is complete, acetonitrile and unreacted raw materials are removed by vacuum distillation, and then dried under vacuum at a vacuum degree of 0.08 MPa and a temperature of 80 °C to obtain 1-hydroxypropyl-3-methylimidazolium ethoxy ether. Preparation of LASTP solid electrolyte sheet: 19g of LASTP and 0.5g of polyvinylidene fluoride (PVDF) are mixed evenly and then placed into a cylindrical mold for tableting. The mixture is then pressed into tablets using a powder tablet press at a pressure of 30MPa and held for 5 minutes to obtain a circular solid electrolyte nucleus with a diameter of 17mm and a thickness of about 0.8mm. The nucleus is then placed in a muffle furnace and heat-treated at 850℃ for 3 hours to obtain LASTP solid electrolyte tablets. Electrode fabrication and battery assembly: 8g of electrode material, 1g of PVDF binder, and 1g of Super P conductive agent were dispersed in 20g of N-methylpyrrolidone solvent. The mixture was stirred continuously on a magnetic stirrer for 12 hours to obtain a uniform slurry. The slurry was then coated onto an aluminum foil current collector and transferred to a vacuum oven to dry at 80°C for 24 hours to remove NMP. Finally, the dried electrode was cut into 12mm diameter coin cell electrode sheets using a manual slicing machine. The battery assembly was carried out in an argon-filled glove box. The above electrode sheets were used as working electrodes, and a lithium sheet with a diameter of 16mm and a thickness of 0.6mm was used as the counter electrode. A CR2025 type coin cell was used to assemble a lithium-ion battery.
[0025] Its lithium-ion transference number was tested to be 0.52, and its room-temperature ionic conductivity was 7.45 × 10⁻⁶. -4 S / cm, particle size D50=0.85 μm.
[0026] Example 2 A method for preparing Sn-doped LATP solid electrolyte includes the following steps: Preparation of LASTP precursor powder: Li was prepared by sol-gel method 1.3 Al 0.3 Sn x Ti 1.7-x (PO4)3 (x=0.14) solid electrolyte, using reagent-grade LiNO3, Al(NO3)•9H2O, SnCl4•5H2O, and C as the Li, Al, Sn, Ti, and P sources, respectively. 12 H 28 O4Ti, NH4H2PO4, first add 450g C 12 H 28 O4Ti was added to 1500g of deionized water and stirred to form titanium hydroxide precipitate. The titanium hydroxide precipitate was washed four times and transferred to an empty beaker. Then, the titanium hydroxide precipitate was added to 550g of HNO3 solution. After a clear solution was formed, 50g of SnCl4•5H2O was added. After complete dissolution, 150g of C6H8O7•H2O, 95g of LiNO3, and 150g of Al(NO3)•9H2O were added sequentially while stirring. After complete dissolution, 400g of NH4H2PO4 was added to the solution to form a sol. After stirring at room temperature for 0.7h, it was allowed to stand for 1.5h to form a gel. The gel was placed in a 90℃ oven and dried for 36h. Finally, the dried gel was placed in a muffle furnace and heat-treated at 700℃ for 4h to obtain the LASTP precursor. 7g of zirconium balls and 1g of material, including 0.3g of liquid ball milling agent, were added and ball milled using a wet ball milling process for 3 hours at a speed of 400 r / min.
[0027] The liquid ball milling agent is an imidazolium hydroxyalkyl ether compound, 1-hydroxypropyl-3-methylimidazolium ethoxy ether, and its preparation method is as follows: A1: Add 13g of N-methylimidazole, 15g of hydroxypropyl glycidyl ether, 0.4g of tetrabutylammonium bromide, and 130g of anhydrous acetonitrile to the reaction vessel and stir until homogeneous. A2: Heat to 55℃ and react at a constant temperature for 7 hours. During the reaction, the epoxy group opens to form an alcohol hydroxyl group. A3: After the reaction was completed, acetonitrile and unreacted raw materials were removed by vacuum distillation, and the product was dried under vacuum at a vacuum degree of 0.09 MPa and a temperature of 85 °C to obtain 1-hydroxypropyl-3-methylimidazolium ethoxy ether. Preparation of LASTP solid electrolyte sheet: 19.5g of LASTP and 0.5g of polyvinylidene fluoride (PVDF) are mixed evenly and then placed into a cylindrical mold for tableting. The mixture is then pressed into tablets using a powder tablet press at a pressure of 40MPa and held for 7 minutes to obtain a circular solid electrolyte nucleus with a diameter of 18mm and a thickness of about 0.9mm. The nucleus is then placed in a muffle furnace and heat-treated at 880℃ for 4 hours to obtain LASTP solid electrolyte tablets. Electrode fabrication and battery assembly: 9g of electrode material, 1.5g of PVDF binder, and 1.5g of SuperP conductive agent were dispersed in 30g of N-methylpyrrolidone solvent. The mixture was stirred continuously on a magnetic stirrer for 18h to obtain a uniform slurry. The slurry was then coated onto an aluminum foil current collector and transferred to a vacuum oven to dry at 90°C for 36h to remove NMP. Finally, the dried electrode was cut into 13mm diameter coin cell electrode sheets using a manual slicing machine. The battery assembly was carried out in an argon-filled glove box. The above electrode sheets were used as working electrodes, and a lithium sheet with a diameter of 16mm and a thickness of 0.6mm was used as the counter electrode. A CR2025 type coin cell was used to assemble a lithium-ion battery.
[0028] Its ion transport number was tested to be 0.6 and its ionic conductivity to be 6.5 × 10⁻⁶. -3 S / cm, particle size D50=0.52 μm.
[0029] Example 3 A method for preparing Sn-doped LATP solid electrolyte includes the following steps: Preparation of LASTP precursor powder: Li was prepared by sol-gel method 1.3 Al 0.3 Sn x Ti 1.7-x(PO4)3 (x=0.25) solid electrolyte, using reagent-grade LiNO3, Al(NO3)•9H2O, SnCl4•5H2O, and C as the Li, Al, Sn, Ti, and P sources, respectively. 12 H 28 O4Ti, NH4H2PO4, first add 500g C 12 H 28 O4Ti was added to 2000g of deionized water and stirred to form titanium hydroxide precipitate. The titanium hydroxide precipitate was washed 5 times and transferred to an empty beaker. Then, the titanium hydroxide precipitate was added to 600g of HNO3 solution. After a clear solution was formed, 105g of SnCl4•5H2O was added. After complete dissolution, 200g of C6H8O7•H2O, 105g of LiNO3 and 190g of Al(NO3)•9H2O were added sequentially and stirred continuously. After complete dissolution, 600g of NH4H2PO4 was added to the solution to form a sol. The mixture was stirred at room temperature for 1 hour and then allowed to stand for 2 hours to form a gel. The gel was dried in a 100℃ oven for 48 hours. Finally, the dried gel was heat-treated in a muffle furnace at 800℃ for 5 hours to obtain the LASTP precursor. 10g of zirconium balls and 1g of material, including 0.4g of liquid ball milling agent, were added and ball milled using a wet ball milling process for 4 hours at a speed of 500 r / min.
[0030] The liquid ball milling agent is an imidazolium hydroxyalkyl ether compound, 1-hydroxypropyl-3-methylimidazolium ethoxy ether, and its preparation method is as follows: A1: Add 15g of N-methylimidazole, 18g of hydroxypropyl glycidyl ether, 0.5g of tetrabutylammonium bromide, and 150g of anhydrous acetonitrile to the reaction vessel and stir until homogeneous. A2: Heat to 60℃ and react at a constant temperature for 8 hours. During the reaction, the epoxy group opens to form an alcohol hydroxyl group. A3: After the reaction is complete, acetonitrile and unreacted raw materials are removed by vacuum distillation, and then dried under vacuum at 0.1 MPa and 90°C to obtain 1-hydroxypropyl-3-methylimidazolium ethoxy ether. Preparation of LASTP solid electrolyte sheet: Mix 20g LASTP and 1g polyvinylidene fluoride evenly, then put them into a cylindrical mold for tableting, and press them into tablets with a pressure of 50MPa using a powder tablet press. Hold the pressure for 10 minutes to obtain a circular solid electrolyte body with a diameter of 19mm and a thickness of about 1mm. Then heat-treat it in a muffle furnace at 900℃ for 5 hours to obtain LASTP solid electrolyte tablets. Electrode fabrication and battery assembly: 10g of electrode material, 2g of PVDF binder, and 2g of SuperP conductive agent were dispersed in 40g of N-methylpyrrolidone solvent. The mixture was stirred continuously on a magnetic stirrer for 24h to obtain a uniform slurry. The slurry was then coated onto an aluminum foil current collector and transferred to a vacuum oven to dry at 100℃ for 48h to remove NMP. Finally, the dried electrode was cut into 15mm diameter coin cell electrode sheets using a manual slicer. The battery assembly was carried out in an argon-filled glove box. The above electrode sheets were used as working electrodes, and a lithium sheet with a diameter of 16mm and a thickness of 0.6mm was used as the counter electrode. A CR2025 type coin cell was used to assemble a lithium-ion battery.
[0031] Its ion transport number was measured to be 0.72 and its ionic conductivity to be 6.2 × 10⁻⁶. -2 S / cm, particle size D50=0.38 μm.
[0032] Comparative Example 1 A method for preparing LATP solid electrolyte includes the following steps: Preparation of LASTP precursor powder: Li was prepared by sol-gel method 1.3 Al 0.3 Sn x Ti 1.7-x (PO4)3 (x=0) solid electrolyte, using reagent-grade LiNO3, Al(NO3)•9H2O, SnCl4•5H2O, and C as the Li, Al, Sn, Ti, and P sources, respectively. 12 H 28 O4Ti, NH4H2PO4, first 400gC 12 H 28 O4Ti was added to 1000g of deionized water and stirred to form titanium hydroxide precipitate. The titanium hydroxide precipitate was washed three times and transferred to an empty beaker. Then, the titanium hydroxide precipitate was added to 500g of HNO3 solution. After complete dissolution, 100g of C6H8O7•H2O, 90g of LiNO3 and 110g of Al(NO3)•9H2O were added in sequence and stirred continuously. After complete dissolution, 300g of NH4H2PO4 was added to the solution to form a sol. The solution was stirred at room temperature for 0.5h and then allowed to stand for 1h to form a gel. The gel was placed in an 80℃ oven and dried for 24h. Finally, the dried gel was placed in a muffle furnace and heat-treated at 600℃ for 3h to obtain the LASTP precursor. Preparation of LASTP solid electrolyte sheet: 19g of LASTP and 0.5g of polyvinylidene fluoride (PVDF) are mixed evenly and then placed into a cylindrical mold for tableting. The mixture is then pressed into tablets using a powder tablet press at a pressure of 30MPa and held for 5 minutes to obtain a circular solid electrolyte nucleus with a diameter of 17mm and a thickness of about 0.8mm. The nucleus is then placed in a muffle furnace and heat-treated at 850℃ for 3 hours to obtain LASTP solid electrolyte tablets. Electrode fabrication and battery assembly: 8g of electrode material, 1g of PVDF binder, and 1g of Super P conductive agent were dispersed in 20g of N-methylpyrrolidone solvent. The mixture was stirred continuously on a magnetic stirrer for 12 hours to obtain a uniform slurry. The slurry was then coated onto an aluminum foil current collector and transferred to a vacuum oven to dry at 80°C for 24 hours to remove NMP. Finally, the dried electrode was cut into 12mm diameter coin cell electrode sheets using a manual slicing machine. The battery assembly was carried out in an argon-filled glove box. The above electrode sheets were used as working electrodes, and a lithium sheet with a diameter of 16mm and a thickness of 0.6mm was used as the counter electrode. A CR2025 type coin cell was used to assemble a lithium-ion battery.
[0033] Its lithium-ion transference number was tested to be 0.4, and its room-temperature ionic conductivity was 5 × 10⁻⁴. -4 S / cm, particle size D50 = 8.5μm.
[0034] Comparative Example 2 A method for preparing Sn-doped LATP solid electrolyte includes the following steps: Preparation of LASTP precursor powder: Li was prepared by sol-gel method 1.3 Al 0.3 Sn x Ti 1.7-x (PO4)3 (x=0.14) solid electrolyte, using reagent-grade LiNO3, Al(NO3)•9H2O, SnCl4•5H2O, and C as the Li, Al, Sn, Ti, and P sources, respectively. 12 H 28 O4Ti, NH4H2PO4, first add 450g C 12 H 28O4Ti was added to 1500g of deionized water and stirred to form titanium hydroxide precipitate. The titanium hydroxide precipitate was washed four times and transferred to an empty beaker. Then, the titanium hydroxide precipitate was added to 550g of HNO3 solution. After a clear solution was formed, 50g of SnCl4•5H2O was added. After complete dissolution, 150g of C6H8O7•H2O, 95g of LiNO3, and 150g of Al(NO3)•9H2O were added sequentially while stirring. After complete dissolution, 400g of NH4H2PO4 was added to the solution to form a sol. After stirring at room temperature for 0.7h, the solution was allowed to stand for 1.5h to form a gel. The gel was dried in a 90℃ oven for 36h. Finally, the dried gel was heat-treated in a muffle furnace at 700℃ for 4h to obtain the LASTP precursor. Preparation of LASTP solid electrolyte sheet: 19.5g of LASTP and 0.5g of polyvinylidene fluoride (PVDF) are mixed evenly and then placed into a cylindrical mold for tableting. The mixture is then pressed into tablets using a powder tablet press at a pressure of 40MPa and held for 7 minutes to obtain a circular solid electrolyte nucleus with a diameter of 18mm and a thickness of about 0.9mm. The nucleus is then placed in a muffle furnace and heat-treated at 880℃ for 4 hours to obtain LASTP solid electrolyte tablets. Electrode fabrication and battery assembly: 9g of electrode material, 1.5g of PVDF binder, and 1.5g of SuperP conductive agent were dispersed in 30g of N-methylpyrrolidone solvent. The mixture was stirred continuously on a magnetic stirrer for 18h to obtain a uniform slurry. The slurry was then coated onto an aluminum foil current collector and transferred to a vacuum oven to dry at 90°C for 36h to remove NMP. Finally, the dried electrode was cut into 13mm diameter coin cell electrode sheets using a manual slicing machine. The battery assembly was carried out in an argon-filled glove box. The above electrode sheets were used as working electrodes, and a lithium sheet with a diameter of 16mm and a thickness of 0.6mm was used as the counter electrode. A CR2025 type coin cell was used to assemble a lithium-ion battery.
[0035] Its ion transport number was tested to be 0.45 and its ionic conductivity to be 5.5 × 10⁻⁶. -4 S / cm, particle size D50=6.2 μm.
[0036] In summary, the liquid ball milling agent and Sn doping described in this invention have a significant synergistic effect.
[0037] Experiments show that Comparative Example 1 (without Sn doping and without liquid ball milling agent) has an ion transport number of only 0.4 and a room temperature ionic conductivity of only 5 × 10⁻⁶. -4 S / cm; After introducing Sn doping alone, its ion transference number only increased to 0.45, and its ionic conductivity only slightly increased to 5.5 × 10⁻⁶. -4The improvement in S / cm is extremely limited, indicating that Sn doping alone is unlikely to achieve a substantial performance breakthrough.
[0038] Without introducing Sn doping, wet ball milling with only the liquid milling agent of this invention resulted in an increase in ion transference number to 0.52 and ionic conductivity to 7.45 × 10⁻⁶. -4 The S / cm indicates that the liquid ball milling agent itself has a significant independent synergistic effect. The mechanism lies in the fact that the liquid ball milling agent can effectively reduce the particle size of the precursor particles and prevent particle agglomeration by forming hydrogen bonds with the precursor particle surface through the alcohol hydroxyl and ether bonds in its molecular structure. This optimizes the electrolyte microstructure and reduces grain boundary resistance. More importantly, when Sn doping is used synergistically with the liquid ball milling agent of this invention, the performance undergoes an order-of-magnitude leap: the ion transference number can reach up to 0.72, and the room temperature ionic conductivity can reach up to 6.2 × 10⁻⁶. -2 The S / cm ratio was approximately 124 times higher than Comparative Example 1, approximately 113 times higher than Comparative Example 2 with Sn doping alone, and approximately 83 times higher than Example 1 using liquid ball milling agent alone. These results indicate that the liquid ball milling agent of the present invention is not only a simple dispersion medium, but its imidazole groups also possess coordination ability, which can promote Sn dispersibility during ball milling. 4+ Uniform doping at Ti sites synergistically optimizes Li + The structural integrity of the migration channel enables a significant leap in ion transport performance.
Claims
1. A method for preparing LATP solid electrolyte, characterized in that, Includes the following steps: LATP solid electrolyte precursors were prepared using the sol-gel method; The LATP solid electrolyte precursor was mixed with a liquid ball milling agent and then wet ball milled to obtain LATP solid electrolyte precursor powder. The LATP solid electrolyte precursor powder was pressed and heat-treated to obtain the LATP solid electrolyte. The liquid ball milling agent contains an imidazole hydroxyalkyl ether compound.
2. The method for preparing LATP solid electrolyte according to claim 1, characterized in that, The imidazole-based hydroxyalkyl ether compound is prepared by a ring-opening addition reaction of N-methylimidazolium with an epoxy-containing hydroxyalkyl ether compound.
3. The method for preparing LATP solid electrolyte according to claim 2, characterized in that, The preparation method of the liquid ball milling agent includes: dissolving N-methylimidazole, an epoxy-containing hydroxyalkyl ether compound and a phase transfer catalyst in an organic solvent, reacting at a high temperature, and obtaining the liquid ball milling agent through post-treatment.
4. The method for preparing LATP solid electrolyte according to claim 3, characterized in that, The epoxy-containing hydroxyalkyl ether compound is hydroxypropyl glycidyl ether, the imidazolium hydroxyalkyl ether compound is 1-hydroxypropyl-3-methylimidazolium ethoxy ether, the phase transfer catalyst is tetrabutylammonium bromide, and the organic solvent is anhydrous acetonitrile. By weight: 10-15 parts of N-methylimidazolium, 12-18 parts of epoxy-containing hydroxyalkyl ether compounds, 0.2-0.5 parts of tetrabutylammonium bromide, and 100-150 parts of anhydrous acetonitrile; The reaction is carried out at a temperature of 50-60°C for 6-8 hours.
5. The method for preparing LATP solid electrolyte according to claim 1, characterized in that, The sol-gel method includes: adding a titanium source to water, stirring to form a titanium hydroxide precipitate, washing it, and then adding it to a nitric acid solution until dissolved; then adding citric acid, a lithium source, and an aluminum source in sequence, dissolving them completely, and then adding a phosphorus source to form a sol. After standing to form a gel, the LATP solid electrolyte precursor was obtained by drying and heat treatment.
6. The method for preparing LATP solid electrolyte according to claim 5, characterized in that, The lithium source is lithium nitrate, the aluminum source is aluminum nitrate nonahydrate, the titanium source is tetrabutyl titanate, and the phosphorus source is ammonium dihydrogen phosphate. The sol-gel method further includes adding a tin source before the sequential addition of citric acid, lithium source, and aluminum source; the tin source is tin tetrachloride pentahydrate. The mass ratio of the lithium source, aluminum source, tin source, titanium source and phosphorus source is 90-105:110-190:0-105:400-500:300-600.
7. The method for preparing LATP solid electrolyte according to claim 5, characterized in that, The sol is stirred at room temperature for 0.5-1 h and then allowed to stand for 1-2 h to form a gel. The gel is dried at 80-100℃ for 24-48 h, and finally the dried gel is heat-treated at 600-800℃ for 3-5 h to form the LATP solid electrolyte precursor.
8. The method for preparing LATP solid electrolyte according to claim 1, characterized in that, The wet ball milling time is 2-4 hours, the ball-to-material mass ratio is 5:1-10:1, and the rotation speed is 300-500 r / min; The pressing pressure is 30-50 MPa, and the holding pressure is 5-10 min; the heat treatment temperature is 850-900℃, and the time is 3-5 h.
9. The LATP solid electrolyte prepared by the preparation method according to any one of claims 1-8.
10. A solid-state battery, characterized in that, Includes the LATP solid electrolyte as described in claim 9.
Citation Information
Patent Citations
Preparation method of lanthanum-doped lithium borate coated LATP solid electrolyte
CN119944051A
LATP solid electrolyte and preparation method and application thereof
CN120089815A